Detection of monodon baculovirus by molecular biology method. - Mohamed Din, Mohamed Shariff; Lee, Kok Leong (2007)

(untitled)
The development of a nested polymerase chain reaction (PCR) assay is described to detect low concentrations of monodon baculovirus (MBV) DNA. A pair of nested promers for detection of monodon baculovirus (MBV) by single - tube single-loading ested PCR is disclosed. The primers are designed from the genomic DNA shrimps and other crustaceans.